Neuroscience and Vygotsky: Putting Together Contemporary Evidence and Cultural-Historical Psychology - Brockington, Guilherme; Moreira, Ana Paula [UNESP]; Veresov, Nikolay (Springer Nature, 2022)
In the early decades of the twentieth century, Lev Semenovich Vygotsky, Alexis Nikolaevich Leontiev, and Alexander Romamovich Luria proposed the so-called Cultural-Historical Psychology. The aforementioned authors took on the challenge of building a psychological theory that would overcome naturalizing, a-historical, and idealistic approaches to human development, in order to apprehend it, considering that human minds shape and are shaped by social, cultural, and historical conditions. Led by Vygotsky, the cultural-historical theory, centered on the processes of thought, language, behavior, and learning, brought great advances to psychology, and since then, this theoretical corpus has been expanded by several researchers, mainly in the area of Education. Simultaneously, it was possible to follow the development of cognitive psychology and neuroscience and their advances in the same areas of Vygotsky’s interest. However, there is practically no academic work that connects Vygostky’s theoretical propositions on human development and contemporary evidence in these research fields. Thus, without intending to make a historical rescue, this text will present several and solid connections between cultural-historical theory and recent findings in cognitive psychology and neuroscience. More than that, we will show that much of what was proposed by Vygostky in the 1920s and 1930s is now part of the theoretical framework of several theories on the functioning of the mind and human development. The main aim of this text is to sensitize researchers in the areas of cognitive psychology and neuroscience to study Vygostky because his theory can contribute to current research.
Keywords: Cultural-Historical Psychology; Human development; Lev Vygotsky; Neuroscience; Psychology